Effect of block of α-1-adrenoceptors on overall motor activity but not on spatial cognition in the object-position recognition task - Levčík, D; Stuchlík, A; Klement, D (Physiological research, 2013)
Prazosin, an alpha(1)-adrenoceptor antagonist, is well known for its depressant effect on motivation and motor activity, while it has no effect on retention of spatial behavior in several tasks, e.g. in the Morris water maze and radial arm maze. The role of alpha(1)-adrenoceptors in operant tasks with stimulus-controlled behavior has not yet been tested. The present study investigated the effect of prazosin on the modulation of overall motor activity and on cognitive performance in a spatial operant task called object-position recognition task, where operant behavior (lever pressing) was controlled by spatial stimuli displayed on a computer screen. This task has been previously showed to be hippocampal-dependent. Pre-test injection of prazosin at the dose of 3 mg/kg decreased the responding rate, while it did not affect the recognition of object's position. In conclusion, we validated the new cognitive test with a drug with known pharmacological effects on behavior and confirmed the depressant effect of prazosin on motor activity and no effect on retrieval of spatial memory in the hippocampal-dependent operant task.
Keywords: Behavior, Animal; Male; Receptors, Adrenergic, alpha-1; Adrenergic alpha-1 Receptor Antagonists; Rats, Long-Evans; rozpoznávání (psychologie); mužské pohlaví; alfa-1-adrenergní receptory - antagonisté; prazosin; krysa rodu Rattus; Hippocampus; kognice; Animals; Space Perception; zvířata; pohybová aktivita; Rats; operantní podmiňování; Motor Activity; chování zvířat; Recognition, Psychology; potkani Long-Evans; vnímání prostoru; alfa-1-adrenergní receptory; hipokampus; Conditioning, Operant; Cognition; Prazosin